Turbidity Trends in 20 Water Treatment Plants Across Sabah, Malaysia: Implications for Sustainable Water Resource Management - Ayog, Janice Lynn; Ngui, Min Fui Tom; Leong, Marieanne Christie (International Journal of Integrated Engineering, 2025)
Water Treatment Plants (WTPs) play a vital role in ensuring safe drinking water by removing contaminants, with turbidity serving as a key indicator of raw water quality. However, turbidity levels in raw water sources are increasingly influenced by extreme weather events and anthropogenic activities, presenting challenges for effective water treatment. This study aims to assess turbidity trends and identify contributing factors in WTPs across Sabah, Malaysia, to support more sustainable water management practices. Turbidity data from the WTPs, spanning 1 to 8 years, were analysed, supplemented by time-lapse satellite imagery to assess upstream catchment conditions wherever possible. Data were categorised into four administrative divisions - West Coast, Kudat, Interior, and Tawau divisions - and examined for temporal and spatial variations. The analysis revealed frequent turbidity spikes, particularly in the Tawau and Interior divisions, with some WTPs, such as Kalabakan and Beaufort I & II, recording levels exceeding 1000 Nephelometric Turbidity Units (NTU), which is the operational shutdown threshold used by WTPs to prevent treatment failure and equipment damage. Kalabakan recorded a peak turbidity of 2,264 NTU, while Beaufort I and II reached 2,528 NTU, more than twice the downtime threshold. These elevated levels were closely linked to extensive land clearing and agricultural activities. The study underscores the importance of integrated water resource management, including erosion control, reforestation, and stricter land-use regulations. To improve operational resilience, real-time turbidity monitoring and predictive modelling are recommended to enhance WTP resilience and ensure a sustainable water supply in tropical regions amidst intensifying environmental pressures.